Assessment of the growth performance and haematological indices of Clarias gariepinus fingerlings exposed to soap effluent - Samuel Olusayo Akinkuolie (SpringerOpen, 2021)
Abstract Background Various substances released from modern complex human societies which enter the aquatic ecosystems produce alterations in survivability of aquatic biota. This study assesses the consequence of exposure to industrial effluents containing potentially hazardous constituents, especially soap industrial waste effluent, relative to fish physiology, growth and survival, particularly food fish such as Clarias gariepinus. Five hundred (500) fingerlings of C. gariepinus (15.65 ± 0.02 g) randomly stocked at 50 fish per tank in duplicates were exposed to varying concentration (0, 0.32, 0.66, 1.31 and 2.63%) of homogenous effluent sample and fed Durante® floating feed at 5% of the body weight in two instalments per day for 180 days. The growth performance and feed utilization data were generated to determine the growth performance indices. The haematological parameters of the fish were also determined following routine methods of fish haematology. Result Generally, fish in the control had significantly (p < 0.05) better growth performance indices compared with the exposed fish. It was also observed that most of the significant increase or decrease observed in the growth performance was concentration dependent. Increase in HES concentration which significantly increases (p < 0.05) WBC count of the experimental fish was observed to decrease (p < 0.05) the HGB level of the fish. Significantly higher (p < 0.05) levels of RBC (3.02 ± 0.03 × 106/µL) and HCT (36.70 ± 1.68%) were recorded in the control fish. However, all the exposed fish had significantly higher (p < 0.05) levels of platelet count compared with the control. Conclusion This study concluded that exposure to concentrations of soap effluent induced stress, inhibited growth and altered the haematological indices of the exposed fish. Uncontrolled discharge of soap effluent into receiving water bodies, apart from affecting the wellbeing of an important freshwater food fish, there is every probability of possible accumulation of the chemical/toxic additives of the soap effluent which could have serious implications considering the man as the major and final recipient of these toxic bioaccumulated chemicals via the food chain and the environment.